Thomas Ebendorfer on virtus sermonis and the Relation between Theology, Philosophy, and Logic: With an Edition of the Prologue to His Commentary on the Sentences. - Curuț, Ioana (Vivarium, 2023)
The focus of this article is the manner in which Thomas Ebendorfer of Hasselbach, a Viennese theologian lecturing on Book I of the Sentences in 1421, deals with the topic of virtus sermonis and the relation between theology, philosophy, and logic in his Prologue from the autograph MS Wien, Österreichische Nationalbibliothek, 4369 (ff. 7–8). By combining a double classification of each science (into acquisita vs. infusa) with a double perspective of their relation (temporal vs. natural), and by making a strong claim for theology's role in advancing new logical theories, Ebendorfer's view reflects a progressive awareness of the distinction between theology and philosophy which, in turn, entails very different applications of virtus sermonis in the two sciences. An edition of the Prologue is provided in the Appendix.